Ammatoa Traditional System: Ethnographic Study of the Values of Social Structure and Environmental Sustainability - Pahenra A Nongko; Tri Indah Rusli; Patta Hindi Asis; Muhammad Agung Maugi; Muhammad Esya Kurniawan (Journal of Innovation in Educational and Cultural Research, 2026)
This ethnographic study investigates the Ammatoa Kajang customary system in South Sulawesi, Indonesia, focusing on its "Pasang" tradition, which promotes simple living, reverence for nature, and resistance to modernization that threatens environmental balance. The research aims to examine the community's social structure, the role of Ammatoa leadership, and the customary rules shaping behavior and environmental interaction. Using participant observation and in-depth interviews with indigenous leaders, the study reveals that the "Pasang" tradition serves as a comprehensive guide for sustainable natural resource management. Customary norms, such as prohibiting tree felling and prioritizing forest conservation, have enabled the community to maintain ecological equilibrium. The findings underscore the significance of local wisdom in supporting environmental sustainability. This research contributes to cultural anthropology education by offering insights into indigenous governance and resilience. It also provides a valuable perspective for conservation policies that recognize and integrate the role of indigenous peoples in safeguarding both natural and cultural heritage.